Application of information technologies in the training process of well-trained kayakers - Zamotin, T. M. (Uchenye zapiski universiteta imeni P.F. Lesgafta, 2021)
Information technology are dynamically introduced into the training process of well-trained athletes, with their assistance, the monitoring of training becomes more informative and individual. The most common means of monitoring are a smart watch, this device can keep a round-the-clock record of training activities and the state of the athlete's body. Such a tool can be useful for trainers when drawing up individual training plans, as it allows you to comprehensively assess the training load and the response to it from the body. The purpose of the research is to develop an approach to monitoring the training load of well-trained kayakers using modern information technology.